2006
DOI: 10.1097/01.brs.0000209304.76581.c5
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid for Hemostasis in the Surgical Treatment of Metastatic Tumors of the Spine

Abstract: Control of operative bleeding in metastatic spine surgery can be problematical. Optimum protocol might include routine preoperative angiographic tumor embolization to decrease lesion vascularity in all cases, but angiography is not without risk. Noninvasive prophylaxis of tumor bleeding would have obvious desirable advantages but was, unfortunately, not achieved in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
(5 reference statements)
1
34
0
Order By: Relevance
“…Bednar et al (20) found that a TXA infusion at a high dose (1 mg/kg/hr) was not superior to a low dose in limiting intraoperative blood loss during spinal surgery. However, for single-dose administration of TXA, a high dosage of TXA (!15 mg/kg) was more effective in reducing total blood loss and the need for blood transfusion in spinal surgery (21).…”
Section: Discussionmentioning
confidence: 98%
“…Bednar et al (20) found that a TXA infusion at a high dose (1 mg/kg/hr) was not superior to a low dose in limiting intraoperative blood loss during spinal surgery. However, for single-dose administration of TXA, a high dosage of TXA (!15 mg/kg) was more effective in reducing total blood loss and the need for blood transfusion in spinal surgery (21).…”
Section: Discussionmentioning
confidence: 98%
“…The literature search yielded a total of eighteen articles that were eligible for analysis 1,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . From those articles, twenty-one independent samples (including seven groups of patients managed with aprotinin, seven groups of patients managed with tranexamic acid, and seven groups of patients managed with epsilon-aminocaproic acid) qualified for inclusion, representing a total of 370, 288, and 308 patients, respectively.…”
Section: Literature Searchmentioning
confidence: 99%
“…45,47 Bednar et al assessed the efficacy of tranexamic acid in decreasing operative blood loss and the need for intraoperative transfusion in metastatic spine surgery but could not shown any benefit of this prophylaxis. 48 It has been observed that limb-saving surgery result in a better functional outcome compared with conditions after amputation. 49 Pring described a good functional result of 77% according to the Musculosceletal Tumor Society Score (MSTS) after chondrosarcoma resection 50 and limb-saving surgery.…”
Section: Introductionmentioning
confidence: 99%